2007
DOI: 10.1111/j.1708-8208.2007.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of NobelDirect Implants: An Analysis of 550 Consecutively Placed Implants at 18 Different Clinical Centers

Abstract: Background: A recently introduced implant, the NobelDirect (Nobel Biocare AB, Göteborg, Sweden), has previously been documented with substantial bone resorption in a large number of operated cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 14 publications
(26 reference statements)
7
83
0
4
Order By: Relevance
“…The success rate of G-NP implants has previously been reported to be lower for 3-mm diameter implants subject to immediate/early loading. 6 However, the results of the present study did not indicate that high stress will always result in overloading-induced bone loss when one-piece implants are used. Another design of one-piece implants showed no significant difference for the stress in the surrounding bone compared to two-piece implants.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The success rate of G-NP implants has previously been reported to be lower for 3-mm diameter implants subject to immediate/early loading. 6 However, the results of the present study did not indicate that high stress will always result in overloading-induced bone loss when one-piece implants are used. Another design of one-piece implants showed no significant difference for the stress in the surrounding bone compared to two-piece implants.…”
Section: Discussionmentioning
confidence: 52%
“…One stated benefit of the one-piece G-NP implant is preservation of the marginal bone level due to the absence of an implant-abutment junction, but some short-term retrospective clinical studies have found these implants to be associated with poor outcomes. 6,12,26,27 The radiographic results indicated the presence of extensive marginal bone loss (>3 mm) around the G-NP implants. The success rate of G-NP implants has previously been reported to be lower for 3-mm diameter implants subject to immediate/early loading.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since the implant surface is the first part to interact with the host, it has been thoroughly investigated in an attempt to hasten the early host-to-implant response [14,15]. The rationale for its modification focuses upon implant interaction with biofluids, which positively alters the cascade of events leading to bone healing and intimate interaction with the surface [16].…”
Section: Surface Treatmentmentioning
confidence: 99%
“…The fabrication of the two ceramic parts with high precision is a technical challenge because of the brittleness of the ceramic. A gap present between the body part and the abutment increases the risk of bacterial accumulation and thus increases the risk of peri-implant inflammation reaction and bone loss [35]. Therefore, this kind of construction does not prevail in the marketplace.…”
Section: Zirconia As Dental Implantsmentioning
confidence: 99%